The TRGB-SBF Project. I. A Tip of the Red Giant Branch Distance to the Fornax Cluster with JWST - Gagandeep S. Anand; R. Brent Tully; Yotam Cohen; Dmitry I. Makarov; Lidia N. Makarova; Joseph B. Jensen; John P. Blakeslee; Michele Cantiello; Ehsan Kourkchi; Gabriella Raimondo (The Astrophysical Journal, 2024)
Differences between the local value of the Hubble constant measured via the distance ladder versus the value inferred from the cosmic microwave background with the assumption of the standard ΛCDM model have reached over 5 σ significance. To determine if this discrepancy is due to new physics or more mundane systematic errors, it is essential to remove as many sources of systematic uncertainty as possible, by developing high-precision distance ladders that are independent of the traditional Cepheid and Type Ia supernova route. Here, we present JWST observations of three early-type Fornax Cluster galaxies, the first of 14 observations from a Cycle 2 JWST program. Our modest integration times allow us to measure highly precise tip of the red giant branch (TRGB) distances and they will also be used to perform measurements of surface brightness fluctuations (SBFs). From these three galaxies, we determine an average TRGB distance modulus to the Fornax Cluster of μ = 31.424 ± 0.077 mag or D = 19.3 ± 0.7 Mpc. With 11 more scheduled observations in nearby elliptical galaxies, our program will allow us to set the zero-point of the SBF scale to better than 2% for more distant measurements, charting a path toward a high-precision measurement of H _0 that is independent of the traditional Cepheid–supernova Ia distance ladder.